Internalisasi Nilai-Nilai Keislaman Perspektif Sosial Kemasyarakatan - Niken Ristianah (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2020)
Islamic religion has a conception of beliefs, rules, norms or ethics which indeed must be believed and implemented consistently. Islamic values ​​are essentially a collection of principles of life, also in the form of teachings about how humans should live life. In the process of internalizing values, the chosen strategies, approaches and methods are needed. Transinternal is one of the appropriate strategies in internalizing religious values. Transinternal strategy is a way to teach values ​​with several stages, namely by carrying out the transformation of values, followed by the transaction of values, and the transinternalisation of values. Islamic values ​​can be actualized through Islamic Religious Education in several environments, both family, school, and community. the three environments must be able to work well together so that the values ​​that have been instilled internalized in the individual so that they will become personalities. The approach to inculcating Islamic values ​​uses the approach to instilling values ​​with a variety of methods, both exemplary, habituation, advice, supervision, and punishment. Strategies that can be used so that the embedded Islamic values ​​are well internalized in individuals, can use a strategy of value transformation, value transactions and value transinternalisation